병원경영의 효율화를 위한 원무프로세스 재설계 - 전제란(Je-Ran Chun) (한국콘텐츠학회 논문지, 7(6), 2007)
Hospital managements are faced with severe competition and need more complicated information systems for its efficiency than before. Hospital managers have to deal with these environments and provide patients with better services than ever to survive. This thesis analyzes and redesigns the hospital administration processes in terms of patient-oriented view. For that purpose we define the processes of the hospital administration using process design tool like ARIS-Toolset. We also introduce basic concepts of Hospital Information Systems(HIS). We finally reviewed the result of reengineering of hospital management process with AHP methodology. 최근 들어 병원들은 심화되는 경쟁 환경에 처하고 있다. 이런 상황에서는 병원의 업무를 환자의 시각에서 조명하고 이를 반영하는 정보시스템을 갖추는 것이 경쟁력 강화에 있어서 필수사항이라 할 것이다. 일부 병원에서는 업무프로세스를 통합하지 않고, 부분적인 정보만을 제공하고 있으며, 정보의 혼재 및 중복으로 환자 및 의료인에게 적절한 정보를 제공하지 못하고 있는 상태이다. 병원의 목적은 환자진료인 만큼 환자정보를 중심으로 병원정보를 재구성하고 그러한 정보를 중심으로 진료 및 관리체계를 구축하는 것이 중요한 병원관리 영역이 될 것이다. 이를 위해 ARIS 툴을 이용하여 원무프로세스를 분석하고 재설계하였다. 외래원무프로세스 재설계후의 결과를 AHP 기법을 통해서 분석하였고 그 결과를 예시하였다.